Influence of Postharvest Natural Softening Conditions on the Nutritional Quality of Safou (Dacryodes edulis H.J.Lam) Flour: Rheological Properties of the Optimized Safou Flour - Alix Ntongme Mboukap; Mathilde Julie Klang; Bilkissou Njapndounke; Marie Madeleine Nanga Ndjang; Serge Cyrille Houketchang Ndomou; Hilaire Macaire Womeni (International Journal of Food Science)
Safou (Dacryodes edulis H.J.Lam) is a seasonal fruit of great importance in the diet and economy of the populations of safou-producing countries. However, the valorization of this fruit is limited due to postharvest losses linked to the softening of the fruit, though this fruit is an essential source of macro- and micronutrients. Thus, this study is aimed at contributing to the valorization of softened safou by determining the optimum softening time, drying time, and temperature for good nutritional and rheological flour. The effects of the softening time, drying time, and drying temperature on the fat, protein, carbohydrate, dietary fibre, water, calcium, phosphorus, and potassium content were studied using the central composite design. The results showed that all the responses were affected by the factors. Also, the softening time of 4.75 days, drying time of 40.55 hours, and drying temperature of 41.83°C were the optimum conditions for producing safou flour with high nutritional value and good rheological properties. These optimum conditions resulted in safou flour with 58.95%, 12.40%, 22.40%, 4.38%, 4.91%, 2207.90 mg/1000 mg, 1898.30 mg/1000 mg, and 478.540 mg/1000 mg as lipid, protein, carbohydrates, fibre, moisture calcium, phosphorus, and potassium content, respectively. In addition, the pasting temperature, peak viscosity, breakdown, holding viscosity, final viscosity, setback, setback ratio, and stability ratio of the aforementioned flour were 50.42°C, 58 cp, 0.5 cp, 57.5 cp, 61.5 cp, 4 cp, 1.07, and 1, respectively. Based on its nutritional value and rheological properties, softened safou flour can be used in food formulation, thus contributing to the valorization of safou fruits.